State and the community of God: political motifs in Romans and the occasion for Romans 13:1-7 - Edward Elliston Morrell (The University of Edinburgh, 2003)
Scholars have frequently debated the occasion for Romans 13:1-7, examining historical, theological, and exegetical reasons for Paul's seemingly quietist stance in this passage. The political contexts of the text in question, however, have not been taken adequately into account. Both at the literary and historical level, political dimensions provided the occasion for Romans 13:1-7. Paul's discussion in Romans ofjudgment and sin, Christ as redeemer, and the community of Christ are framed within the discourse of apocalyptic eschatology, an ideology which critiqued the state by its disjunctive eschatology and radical negation of the present. The recipients ofPaul's letter were also located in Rome, the social and symbolic centre of Roman imperial ideology. These literary and historical contexts created a tension between the claims ofthe gospel and those of Roman imperial ideology. In Romans 13:1-7, Paul responded to this tension, preserving a space for obeying governing authorities in the lives of Christian communities, a space threatened by his own 'political' theology. In the context of his call for obedience, however, Paul encouraged the creation and preservation of a community of God distinct from the world, a community that lived in tension with the present and in hope for the future.